(untitled) (Sains Humanika, 2015)
This study is presents the literature review on the basic ideas of cultural orientation, service quality, adjustment, and satisfaction issues among Mainland Chinese students studying in Malaysian HEIs.Â It starts with discussing the issues related to globalization, HEIs, and international students. After that the theories of cultural orientation, service quality, adjustment, and satisfaction are explained. This is followed by a depiction of the research model, some relevant research findings, and the theoretical framework of this study.